BLACK WOMEN AND EDUCATION: TRAJECTORY AND CHALLENGES - da Silva, André (Revista Gênero e Interdisciplinaridade, 2023)
Prejudice about the female sex has existed for a long time, combined with prejudice against black people, it makes the lives of black women even more difficult, many white and black women fought to conquer their space in society, some with an even greater challenge, to teach. In this work I make a parallel between these great fighters from different locations, many challenges and many achievements were obtained. Many were pioneers in studying, working and getting their space.